The establishment of the Asia‐Pacific Oral Cancer Network—Inaugural stakeholders' Meeting. (24th April 2020) - Syed Mohd Sobri, Sharifah Nur Syamim; Kanapathy, Jananezwary; Liew, Chee Sun; Cheong, Sok Ching
Abstract: The majority of oral cancer cases occur in Asia and the incidence is expected to continue to rise. Oral cancer is amenable to early detection through visual oral examination yet in many Asian countries, the disease presents at a late stage. The barriers to early detection are similar across the Asia‐Pacific countries therefore, strategies to address these could be more effective if there were concerted efforts and joint resources amongst the countries. To facilitate better engagement and collaboration between stakeholders in oral cancer detection and management, the Asia‐Pacific Oral Cancer Network (APOCNET) was established and the inaugural meeting was held in Kuala Lumpur on the 13th to 15th of September 2019. In this meeting, we identified the challenges faced in the early detection and management of oral cancer amongst the stakeholder countries, showcased the successful oral cancer programs in the region and identified strategic areas for collaboration. For this, notable international speakers and those from local universities and the Ministry of Health Malaysia were invited to share their experiences. The lessons learned from our neighbouring countries could lead to the implementation of similar programs that could help reduce the oral cancer burden in the region.